Understanding User Satisfaction and Its Impact on Food Delivery Apps Dependency Among University Students - Kok Ban Teoh; Lyn Liq Ooi; Dwi Nita Aryani; Irdina Zulaikha binti Syukli Noor Azmin; Feng Fang; Guo Yilin; Huang Yuheng; Mifta Darus Salam; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Food delivery applications (FDAs) have become an essential part of modern student life, providing convenience and accessibility in daily consumption patterns. This study aims to examine the factors influencing user satisfaction and how they contribute to students’ dependence on FDAs. Five key variables were analyzed: time saving, price saving, information quality, security system, and safe packaging. Using a quantitative approach, data were collected through structured questionnaires from 244 active student users and analyzed using regression analysis. The results reveal that all five factors positively affect user satisfaction, with time saving (? = 0.313) showing the strongest influence, followed by price saving (? = 0.245), security system (? = 0.211), safe packaging (? = 0.151), and information quality (? = 0.074). These findings suggest that practical efficiency and economic benefits play a more significant role in shaping satisfaction than informational aspects. The study provides valuable implications for FDA providers and app developers to improve service efficiency, enhance user satisfaction, and foster long-term app engagement.